2017
DOI: 10.1080/19411243.2017.1325814
|View full text |Cite
|
Sign up to set email alerts
|

Parental views regarding seating and participation for young children with cerebral palsy

Abstract: Aim: To explore the views of parents regarding seating for children with cerebral palsy.Method: Two interviews with parents were conducted. These were transcribed verbatim and thematic analysis was conducted.Findings: This small study outlines three themes: 'the importance of seating', 'seating and participation', and 'the parental role in supporting participation'. Conclusion:The parents in this study viewed seating as beneficial to support participation by enhancing energy conservation and promoting upper li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This is in line with previous studies by various researchers who have been actively searching for the most suitable choice of ASO for CP patients (Angsupaisal et al, 2017;Chung et al, 2008;Polhan et al, 2019;Ries, Novacheck & Schwartz, 2014;Ryan, 2016;Sahinoglu, Coskun & Bek, 2017;Vekerdy, 2007). The seating orthosis developed by Polhan et al (2019) and Sahinoglu et al (2017) are shown in Figure 1 Based on an interview with parents regarding the seating and engagement of CP patients, Bolas and Boyle (2017) found that using the autonomous mobility and level of social skills of ASO patients is considered meaningful if they can be sociable, learn new skills, be self-sufficient, have fun, and achieve personal objectives. Therefore, Bolas and Boyle indicated that when evaluating the best for CP patients and their families, it is important to figure out what is relevant and important outcomes.…”
Section: Adaptive Seating Orthosis (Aso)supporting
confidence: 83%
See 1 more Smart Citation
“…This is in line with previous studies by various researchers who have been actively searching for the most suitable choice of ASO for CP patients (Angsupaisal et al, 2017;Chung et al, 2008;Polhan et al, 2019;Ries, Novacheck & Schwartz, 2014;Ryan, 2016;Sahinoglu, Coskun & Bek, 2017;Vekerdy, 2007). The seating orthosis developed by Polhan et al (2019) and Sahinoglu et al (2017) are shown in Figure 1 Based on an interview with parents regarding the seating and engagement of CP patients, Bolas and Boyle (2017) found that using the autonomous mobility and level of social skills of ASO patients is considered meaningful if they can be sociable, learn new skills, be self-sufficient, have fun, and achieve personal objectives. Therefore, Bolas and Boyle indicated that when evaluating the best for CP patients and their families, it is important to figure out what is relevant and important outcomes.…”
Section: Adaptive Seating Orthosis (Aso)supporting
confidence: 83%
“…Physical and occupational therapists regularly recommended ASO for CP patients since the 1960s to enhance their function and strengthen their developmental capacities. According to Bolas & Boyle (2017) through overcoming participation barriers in daily life activities such as play, ASO improves the occupational performance of CP patients. In specific, ASO is widely prescribed to strengthen posture in persons with disabilities, while improving volitional upper limb control.…”
Section: Adaptive Seating Orthosis (Aso)mentioning
confidence: 99%
“…This is echoed in earlier work by Sahinoglu et al [33] who found that both adjustable seating and custom molded seating was required for the children with more postural asymmetries, and Neilson et al [34] who reported on improved quality of life and sitting posture through the provision of customized seating for adults with profound postural disabilities. Furthermore, the use of spinal orthoses may improve head control, stability, and arm-hand function of children with CP [35] and ultimately promote participation in activity and reduce pain [36]. The prevalence of pain was reported by 39% of the children and/or their caregivers in this study, similar to Alriksson-Smidt and H€ agglund [9], who found that approximately one third of Swedish children with CP aged 1-14 years had pain, and that the occurrence of pain increased with age.…”
Section: Discussionmentioning
confidence: 99%